Quality of Preservative Smoked Beef using Different Smoked Method - Imam Thohari; Eny Sri Widyastuti; Agustina Widyasworo Kunharjanti; Mohamad Agustomo (Faculty of Animal Science Universitas Brawijaya, 2013)
The purpose of the study was to determine the effect of the smoking traditional and liquid smoking on the quality of smoked beef in terms of the levels of phenol, TBA number, and total microbes. The research method was experiment with completely randomized design pattern factorial (2x3). The first treatment were the preservation of beef with traditional smoked methods and preservation beef with liquid smoked method. The second treatment were the time of storage, namely 0 day, 2 days and 4 days. Each treatment was repeated 3 times. The results showed that the curing method was highly significant (p <0.01) on phenol content and the total microbes, and gave no affect to the TBA number. The highest levels of phenols obtained by the method of liquid smoked with time storage time of 4 days. TBA value and lowest total microbial were obtained from liquid smoked with time storage of 0 day. The conclusion that liquid smoked method was better than the traditional smoked method. Key words: phenol, TBA value, microbial, meat smoke